The Existence of Individual Companies As Legal Entities In Micro and Small Enterprises In Indonesia: A Review of The Problems of The Alter Ego Doctrine - Salma Syakira, Kineisha; Firdaus, Nur Sa’adah; Suryanti, Nyulistiowati; Yuanitasari, Deviana (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2024)
The enactment of the Job Creation Law affects the provisions of Limited Liability Companies. The mechanism for establishing an Individual Company which is explained implicitly in the Company Law and the Job Creation Law raises issues related to the process of organ responsibility in an Individual Company which states that directors can concurrently hold positions as shareholders and vice versa. One of the problems of the presence of Individual Companies in MSEs in Indonesia is the birth of Alter Ego conditions. The solution to limit the unlimited liability of corporate organs is that the government needs to strengthen and reinforce the doctrine of Piercing the Corporate Veil for Individual Companies and provide legal certainty regarding the regulation of corporate organs in the Company Law and Government Regulation No. 8 of 2021. This article examines the existence of individual companies in the context of micro and small businesses in Indonesia. The focus of the analysis lies on the concept of the alter ego doctrine which often becomes a problem in business practice. This research utilizes a document analysis approach and literature study to explore the legal and practical implications of the alter ego doctrine on individual companies in Indonesia. The analysis shows that the alter ego doctrine has a significant impact on the personal liability of micro and small business owners. The implications of these findings are discussed in the context of business regulation and legal protection for micro and small business owners in Indonesia.